Construct validity and reliability of Amharic version of DASS-21 scale among Ethiopian Defense University College of Health Science students - Bitew Sintayehu Tsegaye; Meseret Molla Asemu; Habtamu Belay Hailu (BMC, 2024)
Abstract Background DASS-21 is the common and widely used tool for assessing depression, anxiety and stress. However, its validity and Reliability in Ethiopian Amharic language is not assessed. Objective To translate the DASS-21 and assess its validity and reliability among Ethiopian Defense University college of health science students in Bishoftu, Ethiopia. Method An institutional based cross-sectional study was conducted using a self-administered questionnaire. A total of 435 students from different departments in accordance with their proportional size were participated in this study. As to the sampling technique, the study units were selected from each department and year of study using simple random sampling proportional to size. Confirmatory factor analyses were employed to assess the factor structure and construct validity of Amharic version of the DASS-21. Cronbach alpha coefficient and corrected item total correlation was calculated to assess the internal consistency of Amharic version of DASS-21. Result Among 435 undergraduate students who participated in the study, 246(56.6%) were the age of 18-25 year and majority 347(79.8%) were males. Regarding their year of study; 200 (46.0%) were first year students. Confirmatory factor analysis indicates a good model fit of the three correlated factors (Comparative fit index (CFI) = 0.92 with root mean square error of approximation (RMSEA) = 0.059[0.052-0.066] and standardize root mean residual SRMR = 0.045). The internal consistency of overall DASS-21 and each sub scale were in acceptable range (0.91, 0.82, 0.77 and 0.77) respectively. Conclusion Amharic version of DASS-21 was found to be a valid and reliable instrument to measure the mental problem especially, Depression, Anxiety and Stress among university students.